Can Lawlike Rules Emerge without the Intervention of Legislators? - Troitzsch, Klaus G. (Frontiers in Sociology, 2018)
The paper shows that in an artificial society lawlike rules emerge “as a result of individual action but without being designed by any individual” agents (Hayek, 1944, p. 288) and discusses earlier literature on the topic. The first example that this paper uses is an artificial society of car drivers moving between their homes and their working places on streets with two lanes crossing each other at right angles. Car drivers start using the left or right lane of the street at random and continue to use the same side of the street until they are stopped by an oncoming car. In this occasion, one of them decides to change to the other side of the street, taking into account which side of the street is used by the locally visible majority. This very simple behavior usually results in a society-wide applied rule: always using the same side of the street. How long it takes for all car drivers to abide by the emerged rule (and how many, if not all, apply the rule) depends on the density of traffic and the range of vision of the car drivers as well as on the distance the cars went. A second example of emerging rule-consistent behavior discussed in the paper and analyzed with different mathematical and computational methods is derived from a model of the emergence of aggression aversion extended to a model of the emergence of a rule against theft and of a rule in favor of almsgiving. In this model, agents receive comments on their theft and alms related actions and form a normative board that controls their propensity to act with respect to theft, prosecuting and punishing theft, asking for and granting alms. This model shows an emerging anti-theft norm whose salience among the agents increases in a rapid transition after a fairly long initial phase during which theft is more or less tolerated.